NITRILASE1 regulates the exit from proliferation, genome stability and plant development. Issue 3 (25th February 2013) - Doskočilová, Anna; Kohoutová, Lucie; Volc, Jindřich; Kourová, Hana; Benada, Oldřich; Chumová, Jana; Plíhal, Ondřej; Petrovská, Beáta; Halada, Petr; Bögre, László; Binarová, Pavla
Summary: Nitrilases are highly conserved proteins with catabolic activity but much less understood functions in cell division and apoptosis. To elucidate the biological functions of Arabidopsis NITRILASE1, we characterized its molecular forms, cellular localization and involvement in cell proliferation and plant development. We performed biochemical and mass spectrometry analyses of NITRILASE1 complexes, electron microscopy of nitrilase polymers, imaging of developmental and cellular distribution, silencing and overexpression of nitrilases to study their functions. We found that NITRILASE1 has an intrinsic ability to form filaments. GFP‐NITRILASE1 was abundant in proliferating cells, distributed in cytoplasm, in the perinuclear area and associated with microtubules. As cells exited proliferation and entered differentiation, GFP‐NITRILASE1 became predominantly nuclear. Nitrilase silencing dose‐dependently compromised plant growth, led to loss of tissue organization and sustained proliferation. Cytokinesis was frequently aborted, leading to enlarged polyploid cells. In reverse, independently transformed cell lines overexpressing GFP‐NITRILASE1 showed slow growth and increased rate of programmed cell death. Altogether, our data suggest that NITRILASE1 homologues regulate the exit from cell cycle and entry into differentiation and simultaneously are required for cytokinesis. These functions are essential to maintain normal ploidy, genome stability and tissue organization.